E-Jawi - Mohd Shafie, Mohamad Faizal; Nazim, Nur Husnina; Rusdi, Nur Athirah; Mohd Tahir, Noor Fathinie; Arif, Zuraidah (Universiti Teknologi MARA, Kedah, 2017)
In this era globalization, children are hooked on their gadgets such as smartphones and tablets. They are do not exposed to Islamic based application that teaches them the basic of Jawi. Jawi writing is important for children as it will allow them to learn tajwid and read Quran. In addition, they are able to recite basic surah such as al-Fatiha which is an important surah in performing prayers. It has also been proven that children tend to understand more when education is done in an interactive way. The purpose of this multimedia learning is to help children to understand better and be able to read Quran in Jawi. Children learn better through images, video, sound and animations compared to learning in the old school way which is by books only. It also help to boost the children’s mood to learn and they will be more proactive.